Immunohistochemical Analysis of the Activation Status of the Akt/mTOR/pS6 Signaling Pathway in Oral Lichen Planus - Georgios Prodromidis; Nikolaos G. Nikitakis; Alexandra Sklavounou (Hindawi Limited, 2013)
Introduction. Aberrations of the Akt/mTOR/pS6 pathway have been linked to various types of human cancer, including oral squamous cell carcinoma (OSCC). The purpose of this study was to evaluate the activation status of Akt, mTOR, and pS6 in oral lichen planus (OLP) in comparison with oral premalignant and malignant lesions and normal oral mucosa (NM). Materials and Methods. Immunohistochemistry for p-Akt, p-mTOR, and phospho-pS6 was performed in 40 OLP, 20 oral leukoplakias (OL), 10 OSCC, and 10 control samples of NM. Results. Nuclear p-Akt expression was detected in the vast majority of cases in all categories, being significantly higher in OL. Cytoplasmic p-Akt and p-mTOR staining was present only in a minority of OLP cases, being significantly lower compared to OL and OSCC. Phospho-pS6 showed cytoplasmic positivity in most OLP cases, which however was significantly lower compared to OL and OSCC. Conclusions. Overall, cytoplasmic p-Akt, p-mTOR, and phospho-pS6 levels appear to be significantly lower in OLP compared to OL and OSCC. However, the expression of these molecules in a subset of OLP cases suggests that activation of Akt/mTOR/pS6 may occur in the context of OLP, possibly contributing to the premalignant potential of individual cases.